2018
DOI: 10.1371/journal.pone.0201673
|View full text |Cite
|
Sign up to set email alerts
|

Clinical magnetic resonance-enabled characterization of mono-iodoacetate-induced osteoarthritis in a large animal species

Abstract: IntroductionOsteoarthritis (OA) is the most common form of arthritis. Medical and surgical treatments have yet to substantially diminish the global health and economic burden of OA. Due to recent advances in clinical imaging, including magnetic resonance imaging (MRI), a correlation has been established between structural joint damage and OA-related pain and disability. Existing preclinical animal models of OA are useful tools but each suffers specific roadblocks when translating structural MRI data to humans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…16,25,27,29 The tissue injury resulting from MIA-induced osteoarthritis in the swine knee has been characterized previously by using clinical-grade 3-T MRI and gross pathologic examination. 28 We found that MIA stimulates initial synovitis, manifest as joint effusion, followed by progressive cartilage erosion, bone marrow edema, and exposure of subchondral bone. Each of these changes has been observed in human osteoarthritis and is considered to be a contributor to chronic, osteoarthritis-related pain syndromes.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…16,25,27,29 The tissue injury resulting from MIA-induced osteoarthritis in the swine knee has been characterized previously by using clinical-grade 3-T MRI and gross pathologic examination. 28 We found that MIA stimulates initial synovitis, manifest as joint effusion, followed by progressive cartilage erosion, bone marrow edema, and exposure of subchondral bone. Each of these changes has been observed in human osteoarthritis and is considered to be a contributor to chronic, osteoarthritis-related pain syndromes.…”
mentioning
confidence: 72%
“…To reduce the number of animals used for related studies, swine were simultaneously enrolled in a separate protocol to study knee imaging and gross pathology, where additional animal-specific information including weight has been reported. 28 Experimental data contained herein have not previously been reported.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations